ChemInform Abstract: Development of Double‐Perovskite Compounds as Cathode Materials for Low‐Temperature Solid Oxide Fuel Cells. Issue 10 (March 2015) - Yoo, Seonyoung; Jun, Areum; Ju, Young‐Wan; Odkhuu, Dorj; Hyodo, Junji; Jeong, Hu Young; Park, Noejung; Shin, Jeeyoung; Ishihara, Tatsumi; Kim, Guntae
Abstract NdBa1‐xCaxCo2O5+ δ (x = 0, 0.25) are prepared by a glycine‐nitrate combustion process using an aqueous solution of stoichiometric amounts of Nd(NO3)3, Ba(NO3)2, Ca(NO3)2, Co(NO3)2, and a proper amount of glycine.